THE ECONOMY OF ZAKAT AND WAQF - Abdul Ghafar Ismail (Dewan Bahasa dan Pustaka, 2022)
This book is intended to develop some important discourses on important subjects, that is, tawhid, zakat, and waqf. Islam has placed a central focus on poverty alleviation to establish dignity and self-reliance through a consciously participatory development agenda. The principles underlying all these are the organic way of examining the unification of knowledge in learning systems that emanate from and sustain participatory development involving interrelationships between the poor and all others. Such a synergetic learning process is the organic meaning of the unity of knowledge between development systems. It presents the epistemology of unity of the divine law, here understood as the functional ontology manifesting Tawhid (unity of Allah and hence of the divine laws) in the order of the world systems. While zakat, the Islamic claim on Muslim wealth and savings to finance specific programs to alleviate poverty, and Waqf in its physical and cash representations of endowment are specific instruments for poverty alleviation. But for these instruments to attain their full potential new horizons of worldview are needed that inculcate not simply the instrumentation but also the total spirit underlying the instruments, institutions, organizations, states, markets, spending and behavior, and applications so as to bring them together into sustainable participatory development.